Clinical Dermatology Trials 101 : A Primer for Dermatologists - Nasir, Adnan (Springer International Publishing : Imprint: Springer, 2015)
Clinical Dermatology Trials 101 provides dermatologists with a handbook that allows them to become familiar with all aspects of clinical trials. Everything from obtaining the necessary tools and equipment, complying with local, federal, and international guidelines and regulations, and hiring and training staff for the safe and up-to-date conduct of dermatology clinical trials is covered.  Written by leading experts in the field, Clinical Dermatology Trials 101 is the only clinical trial how-to available for dermatologists. With skin disease affecting nearly seventy percent of the population over a lifetime, and the rate of development of new drugs and devices for dermatologic use increasing at an exponential rate, there is a tremendous need for training and developing dermatology clinical research facilities to expedite the translation of basic and applied research, from bench to bedside.  This is useful for practicing dermatologists, academic dermatologists, dermatology residents, clinical research fellows, dermatology fellows, research scientists, industry dermatologists, and medical students.